PENGARUH POLA ASUH DEMOKRATIS DAN STATUS SOSIAL EKONOMI ORANGTUA TERHADAP KEMANDIRIAN ANAK USIA DINI - Hana Ika Safitri (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2021)
This study aims to find out the influence of socioeconomic status of parents and democratic parenting patterns on early childhood independence. The type of research used is quantitative research with ex-post facto research design. Research site in Sanden Subdistrict Kindergarten. The research population consisted of parents and students of about 640 people from 26 kindergarten institutions. Sampling technique using probability sampling technique is cluster random sampling. The number of research samples used by 247 people was calculated using the Slovin formula. Data collection using questionnaires and through observation. Questionnaires are used to obtain data on democratic parenting patterns applied to early childhood as well as the socioeconomic status of parents. Observation is used to observe the independence of early childhood. Validate test using Gregory formula. Data analysis u sing quantitative descriptive analysis and dual regression tests assisted by SPSS21 software. The result of significance or probability of 0.000 < 0.05, then the hypothesis is accepted or socioeconomic status and democratic parenting patterns together can affect the independence of the child. The conclusion of research shows that socioeconomic status and democratic parenting patterns affect the independence of early childhood.